Commentary Article: Study Protocol for the Respond to Prevent Study: A Multi-State Randomized Controlled Trial to Improve Provision of Naloxone, Buprenorphine and Nonprescription Syringes in Community Pharmacies. Issue 1 (December 2022) - Green, Traci C.; Bratberg, Jeffrey; Irwin, Adriane N.; Boggis, Jesse; Gray, Mary; Leichtling, Gillian; Bolivar, Derek; Floyd, Anthony; Al-Jammali, Zain; Arnold, Jenny; Hansen, Ryan; Hartung, Daniel
Access to the opioid antidote naloxone is a critical component of addressing the opioid crisis. Naloxone is a population-level prevention intervention associated with substantial reductions in overdose mortality and reduction of nonfatal overdose. Pharmacies' pivotal role in dispensing medications like buprenorphine for the treatment of opioid use disorder and selling nonprescription syringes places them at the crossroads of opioid access and risk mitigation methods like naloxone provision. Testing ways to optimize pharmacy-based naloxone provision will be key as the country expands the implementation of naloxone through the medical system. In the Respond to Prevent Study, we conducted a large, practical study of a pharmacy-focused intervention in a sample of Washington, Oregon, Massachusetts and New Hampshire community chain pharmacies to increase naloxone dispensing and improve opioid safety. The intervention integrated two evidence-based educational toolkits and streamlined materials to enhance the focus on naloxone policy, stigma reduction, and patient communications around naloxone, nonprescription syringes and buprenorphine access. The real-world study implemented a stepped wedge, clustered randomized trial design across 175 community chain pharmacies to evaluate the effectiveness of the Respond to Prevent intervention in increasing: (a) pharmacy based naloxone distribution rates, naloxone-related patient engagement, and pharmacist and technicians' attitudes, knowledge, perceived behavioral control and self-efficacy toward naloxone; and (b) pharmacy nonprescription syringe sales, and pharmacist and technicians' attitudes, knowledge, perceived behavioral control and self-efficacy toward dispensing buprenorphine for opioid use disorder (secondary outcomes). This commentary provides a brief narrative about the study and presents insights on the design and adaptations to our study protocol, including those adopted during the unprecedented COVID-19 pandemic further compounded by Western wildfires in 2020.